2001
DOI: 10.1007/bf03402183
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Complement Cascade in Ischemia/Reperfusion Injury: Implications for Neuroprotection

Abstract: Background: The complement cascade plays a deleterious role in multiple models of ischemia/reperfusion (I/R) injury, including stroke. Investigation of the complement cascade may provide a critical approach to identifying neuroprotective strategies that can be effective at clinically relevant time points in cerebral ischemia. This review of the literature describes the deleterious effects of complement activation in systemic I/R models and previous attempts at therapeutic complement inhibition, with a focus on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
81
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(83 citation statements)
references
References 128 publications
1
81
0
1
Order By: Relevance
“…However, many of them can be synthesized locally in the brain as well (Barnum 1995;Gasque et al 1995;Morgan and Gasque 1996;Nataf et al 1999). The abnormality of the complement system has been reported in brain injury and neurodegenerative disease (D'Ambrosio et al 2001;Gasque 2004), including AD. In the brain of AD patient, it has been observed that the expression of C1q, C3b, C4d and C5b-9 is elevated, and the MAC colocalizes with senile plaques and tangle-positive neurons (Blalock et al 2004;Fonseca et al 2004;Katsel et al 2009;Shen et al 2001).…”
Section: Neuronmentioning
confidence: 99%
“…However, many of them can be synthesized locally in the brain as well (Barnum 1995;Gasque et al 1995;Morgan and Gasque 1996;Nataf et al 1999). The abnormality of the complement system has been reported in brain injury and neurodegenerative disease (D'Ambrosio et al 2001;Gasque 2004), including AD. In the brain of AD patient, it has been observed that the expression of C1q, C3b, C4d and C5b-9 is elevated, and the MAC colocalizes with senile plaques and tangle-positive neurons (Blalock et al 2004;Fonseca et al 2004;Katsel et al 2009;Shen et al 2001).…”
Section: Neuronmentioning
confidence: 99%
“…[1][2][3][4][5] Deposition of complement-activation products has been shown in Alzheimer's disease, 6,7 ischemia/reperfusion injury, 8 Huntington's and Prion disease, 9,10 and multiple sclerosis (MS). [11][12][13][14][15] In the immune-mediated inflammatory demyelinating disease, multiple sclerosis, and its animal model, experimental autoimmune encephalomyelitis (EAE), myelin, and oligodendrocytes are primary targets of damage.…”
mentioning
confidence: 99%
“…However, the precise roles of various proinflammatory mediators, including cytokines, chemokines and immune cells, are still largely unknown. Increasing evidence suggests that the activation of the complement cascade contributes to pathological inflammatory events in brain (upregulation of adhesion molecules, immune cell activation, chemotaxis, expression of IL-8 and MCP-1 by endothelial cells) (D'Ambrosio et al, 2001), resulting in ischemic insult, neurodegeneration and stroke development. Following brain I/R injury ROS, RNS as well as oxygen free radicals are generated by activated brain cells and infiltrating immune cells, which stimulate stroke-associated brain injury (Elsner et al, 1994, McColl et al, 2009).…”
Section: Strokementioning
confidence: 99%
“…Ischemic stroke enhances interaction between endothelial cells, brain cells, and immune cells that may aggravate the injury process (Urra et al, 2009). All these strokeassociated brain pathologies are function of C3a-C3aR and C5a-C5aR interactions (D'Ambrosio et al, 2001). Strong C3a and C5a activation is observed in patients with acute ischemic stroke, which correlates with disease severity (Szeplaki et al, 2009).…”
Section: Strokementioning
confidence: 99%